2021
DOI: 10.46586/tches.v2022.i1.630-656
|View full text |Cite
|
Sign up to set email alerts
|

Composite Enclaves: Towards Disaggregated Trusted Execution

Abstract: The ever-rising computation demand is forcing the move from the CPU to heterogeneous specialized hardware, which is readily available across modern datacenters through disaggregated infrastructure. On the other hand, trusted execution environments (TEEs), one of the most promising recent developments in hardware security, can only protect code confined in the CPU, limiting TEEs’ potential and applicability to a handful of applications. We observe that the TEEs’ hardware trusted computing base (TCB) is fixed at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…CVA6 host core CVA6 [44] is the heart of Shaheen. It is an open-source 6-stages, single-issue, in-order, 64-bit Linux-capable RISC-V core, supporting the RV64GC ISA variant, SV39 virtual memory with a dedicated Memory Management Unit (MMU), three levels of privilege (Machine, Supervisor, User), and PMP [19]. In the context of this work, the baseline version of CVA6 has been enhanced with 2 extra features to provide high-assurance isolation between the different applications coexisting on the core:…”
Section: Shaheen Architecurementioning
confidence: 99%
See 1 more Smart Citation
“…CVA6 host core CVA6 [44] is the heart of Shaheen. It is an open-source 6-stages, single-issue, in-order, 64-bit Linux-capable RISC-V core, supporting the RV64GC ISA variant, SV39 virtual memory with a dedicated Memory Management Unit (MMU), three levels of privilege (Machine, Supervisor, User), and PMP [19]. In the context of this work, the baseline version of CVA6 has been enhanced with 2 extra features to provide high-assurance isolation between the different applications coexisting on the core:…”
Section: Shaheen Architecurementioning
confidence: 99%
“…In particular, the Hypervisor extension aims to provide confidentiality and integrity of virtual machines (VM) by enforcing isolation (via two-stage virtual memory) between multiple consolidated guest OSes, i.e., General Purpose OS (GPOS) and RTOS. To further isolate the execution of these coexisting software stacks (trusted and untrusted), prevent security threats, and ensure multi-domain operations, the host core features Physical Memory Protection (PMP) [19] and ISA and micro-architecture extensions for timing channel mitigation [20]. Namely, the PMP aims to provide confidentiality and integrity by limiting the physical addresses accessible by software running on CVA6.…”
Section: Introductionmentioning
confidence: 99%
“…Another line of research has shown the feasibility of doing enclaved execution on unmodified devices by extending the CPU-TEE protection. They leverage MMU protection to protect memory-mapped devices and perform bus-level isolation since devices are physically connected to a TEE host [35][36][37].…”
Section: Related Workmentioning
confidence: 99%
“…One potential solution to address this problem is to make all nodes TEE-enabled, but this is not a practical. For protecting non-TEE nodes, prior works have shown the feasibility of doing so via bus-level isolation if they are directly physically connected to a TEE host [35][36][37]. Such host-centric solutions do not apply to a data-center setting where nodes are connected in clusters and racks as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%